1995
DOI: 10.1097/00005373-199507000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Attenuates the Depressed Endothelial Cell Function and Vascular Muscle Contractility following Trauma and Hemorrhagic Shock

Abstract: Although pentoxifylline (PTX) produces various beneficial effects following adverse circulatory conditions, it is not known whether this agent attenuates the depressed vascular endothelial cell function [i.e., the reduced release of endothelium-derived nitric oxide (EDNO)] and smooth muscle contractility after trauma and hemorrhage. To study this, rats underwent a midline laparotomy (i.e., trauma induced) and were bled to and maintained at a mean arterial pressure of 40 mm Hg until 40% of maximal shed volume w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Reversing small intestinal vasoconstriction to prevent post-RES hypoperfusion has been achieved using agents including heparan sulfate, heparin, and pentoxifylline (10,41,43). We have focused on DPR to reverse the post-RES vasoconstriction in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Reversing small intestinal vasoconstriction to prevent post-RES hypoperfusion has been achieved using agents including heparan sulfate, heparin, and pentoxifylline (10,41,43). We have focused on DPR to reverse the post-RES vasoconstriction in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…A study using galactose clearance as an index of nutrient blood flow to liver demonstrated the improved restoration of blood flow to liver when pentoxifylline was administered during resuscitation of hemorrhagic shock [34]. Endothelium-dependent vascular relaxation and antagonist-induced vascular smooth muscle contractility (as indexes of endothelial function) have been shown to be preserved when pentoxifylline was used during resuscitation of hemorrhagic shock [35]. Pentoxifylline has been shown to reduce leukocyte adhesiveness to nylon wool columns, encountered after resuscitation of hemorrhagic shock [36].…”
Section: Fig 1-continuedmentioning
confidence: 99%
“…Indeed, Lefer et al [35] reported that ACh-mediated endotheliumdependent relaxation of isolated aortic rings from cats, was impaired in the presence of TNFα. In addition, Wang et al demonstrated that the administration of TNFα to rats can induce endothelial dysfunction [25], that pentoxifylline reduces plasma TNFα [36], and that the impaired endothelial function associated with elevated TNFα [37] is improved by pentoxifylline [38]. Collectively, these studies suggest down-regulation of TNFα as a possible mechanism for the improvement in endothelial function observed with pentoxifylline.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of incubated cat aortic rings, the effect of TNFα was dose-dependent and µg : ml −" , rather than pg : ml −" , concentrations were required to induce depression of endothelial function [35]. In addition, animal studies indicating that pentoxifylline can improve endothelial function were performed on a model of sepsis [38] which is associated with markedly enhanced TNFα production and much higher circulating levels [39] than studies have typically found in obese insulin-resistant subjects in whom TNFα is putatively derived from adipocytes [40].…”
Section: Discussionmentioning
confidence: 99%